(untitled) (Journal of Applied Learning and Teaching, 2024)
This paper shares an innovative use of an online decision-based simulation to help preservice teachers examine contentious issues, such as challenged books in elementary and middle school classrooms. Challenged books, particularly those around gender diversity topics, can be contentious as well as emotionally laden. The online simulation that uses a combination of recorded actors, writing exercises, and various decision paths requires the preservice teachers to contend with multiple stakeholders and various priorities in a rich sociocultural context. The teacher educators share key strengths of this use that include using a mistake-friendly learning environment, replaying the simulation multiple times to connect decisions with consequences, and engaging in a complex, nuanced, and responsive learning context. This article provides an overview of the simulation and what was found to be useful when using simulations to address contentious topics.